Family Functioning, Identity Commitments, and School Value among Ethnic Minority and Ethnic Majority Adolescents. - Mastrotheodoros, Stefanos; Hillekens, Jessie; Miklikowska, Marta; Palladino, Benedetta Emanuela; Lionetti, Francesca (Journal of Youth & Adolescence, 2024)
Ethnic minority youth show worse school adjustment than their ethnic majority peers. Yet, it remains unclear whether this gap can be explained by differences in family functioning and consequent identity commitments. This study examined (1) whether family functioning relates to identity commitments over time and (2) whether identity commitments impact later school value (3) among minority and majority adolescents. Minority (N = 205, M = 16.25 years, 31.1% girls) and majority adolescents (N = 480, M = 15.73 years, 47.9% girls) participated in this preregistered three-wave longitudinal study (T1: March-April 2012; T2: October 2012; T3: March-April 2013). Dynamic Panel Models revealed that most within-person cross-lagged associations were not significant in the total sample. Yet, multigroup analyses revealed differences between groups: Stronger identity commitments related to lower school value among minority adolescents, but were unrelated to school value among majority adolescents over time. Additionally, higher school value increased identity commitments among minority youth, yet it decreased identity commitments among majority youth over time. The findings highlight the differential interplay between identity commitments and school adjustment for minority and majority adolescents, with important implications for their future life chances.